2022
DOI: 10.1002/pits.22736
|View full text |Cite
|
Sign up to set email alerts
|

Sympathy and active defending behaviors among Chinese adolescent bystanders: A moderated mediation model of attitude toward bullying and school connectedness

Abstract: This study tested the mediating role of bullying attitudes and moderating role of school connectedness in the link between sympathy and Chinese adolescents’ active defending behaviors in bullying. Participants were 808 Chinese adolescents (53.3% male, Mage = 12.40, SD = 0.50). The results showed that sympathy was significantly positively correlated with active defending behaviors through bullying attitudes. In addition, school connectedness could moderate the relationship between sympathy and active defending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…In addition, students who are more attached to school are more likely to believe in the school’s values and rules, and such rule following may promote school safety. School attachment may also promote school safety through encouraging students to intervene when they observe other students behaving in antisocial ways (Feng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, students who are more attached to school are more likely to believe in the school’s values and rules, and such rule following may promote school safety. School attachment may also promote school safety through encouraging students to intervene when they observe other students behaving in antisocial ways (Feng et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Participants stated how often (during the last 3 months) they had acted on the behavior described in each item on a four-point scale (1 = never, 4 = almost always). The Chinese version of this scale has been widely used in previous research and has shown good reliability and validity (47,62,63). For active defending behaviors, Cronbach's alpha was 0.77 for both T1 and T2.…”
Section: Bullying Bystander Behaviorsmentioning
confidence: 99%